Clinical profile of babies with meconium stained amniotic fluid - Ranee, Defairlin; Phirke, Deepa S. (International Journal of Research in Medical Sciences, 2017)
Background: Meconium staining of amniotic fluid (MSAF) is a relatively common problem occuring in 10-25% of all deliveries. Meconium aspiration syndrome is more common in term babies than in preterm babies with rising frequency along with increase in gestational age of the fetus. Meconium stained amniotic fluid generally indicates sign of fetal distress. The objective of this study was to study clinical profile of meconium aspiration syndrome and the probable risk factors for meconium aspiration syndrome. Methods: It is a prospective observational sectional study conducted in NICU of department of paediatrics of tertiary care centre from 1st January 2015 to 30th June 2016. Results: In this study both sexes were equally affected, majority of the neonates were above 2.5kg and only very few (2 neonates) were less than 1.5kg. majority of the neonates were full term, it was found that there is a significant association between thick MSAF and the development of MAS, it was found that there is a significant association between low APGAR score at 1 minutes and the development of MAS, there is a strong association between thick MSAF and mortality in MSAF babies. Anemia 38 (25%) was the most frequent perinatal risk factor followed by fetal distress 27 (18) and PIH 21 (14%). Conclusions: Newborns with thick MSAF were more likely to develop MAS and thick MSAF and low APGAR at 1 min were associated with high risk of development of MAS. Passage of thick meconium was significantly associated with severe birth asphyxia and carried a bad prognosis with increased risk of development of meconium aspiration syndrome and hypoxic ischaemic encephalopathy.